Reputasi dan Citra Rumah Baca Indonesia ke-28 Sebagai Ruang Belajar Komunitas Yang Ramah - Erwin Manik; Nadya Jania; Nelly Armayanti; Nopitasari Manurung (Jurnal Administrasi Perkantoran, 2025)
This study describes the reputation and image of Rumah Baca Indonesia 28 as a community learning space. A qualitative descriptive method was applied through observation, interviews, and documentation. The results indicate that the reading house has a positive reputation supported by consistent learning services, transparent communication, and committed organizers. Its positive image appears through an orderly environment, creative literacy activities, digital media use, and volunteer involvement. The study concludes that reputation and image influence public trust and participation. Improvements in facilities, collaboration, and digital publication are recommended.